2022
DOI: 10.3390/ma16010205
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Surface Impedance in MgB2 in DC Magnetic Fields: Insights in Flux-Flow Resistivity

Abstract: We present the multifrequency measurements of the surface resistance of spark-plasma-sintered MgB2 performed through a dielectric loaded resonator operating at 16.5 and 26.7 GHz. By normally applying magnetic fields ≤1.2 T to the sample surface, we drove it in the mixed state. By means of data-rooted analysis, we found that the sample vortex dynamics could be fully described within a single-component approach. Pinning phenomena were present and characterized by a depinning frequency smaller than the measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…This feature will prove extremely valuable in the forthcoming design process. Moreover, it has been shown that multifrequency measurements of the surface impedance are of great interest in the study of superconductors [15], [16]. Hence, this becomes an additional design goal, so we choose the TE021 mode as a second operating mode, since it shares (same third index) the same longitudinal configuration and thus induces the same current pattern on the lateral wall.…”
Section: Definition Of the Dr Geometrymentioning
confidence: 99%
“…This feature will prove extremely valuable in the forthcoming design process. Moreover, it has been shown that multifrequency measurements of the surface impedance are of great interest in the study of superconductors [15], [16]. Hence, this becomes an additional design goal, so we choose the TE021 mode as a second operating mode, since it shares (same third index) the same longitudinal configuration and thus induces the same current pattern on the lateral wall.…”
Section: Definition Of the Dr Geometrymentioning
confidence: 99%